1993
DOI: 10.1525/aa.1993.95.1.02a00020
|View full text |Cite
|
Sign up to set email alerts
|

Theories of Modern Human Origins: The Paleontological Test

Abstract: N A FIELD OFTEN ACCUSED of being unable to settle controversies or resolve competing I hypotheses, the recent proposal based on interpretations of mitochondria1 DNA (mtDNA) allows for the unambiguous testing of two models about the origin of modern Homo sapiens. These are the total replacement ("Eve") and the continuity (multiregional evolution) models, both of which have clearly definable, completely different predictions about the pattern ofpast evolution, as well as different expectations about the distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
102
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(104 citation statements)
references
References 92 publications
0
102
0
2
Order By: Relevance
“…However, this prediction is misleading. As we have pointed out elsewhere (Stringer and Brä uer, 1994;Brä uer and Stringer, 1997;Stringer, 2002), the idea of complete replacement without any interbreeding is one variant of the Out of Africa hypothesis, often identified with a particular interpretation of the mitochondrial DNA data, dubbed the Eve theory (Frayer et al, 1993). Complete replacement does not feature in all versions of the Out of Africa hypothesis, and therefore we contend that it would not be falsified by demonstration of some modern-archaic human gene flow outside of Africa.…”
Section: Predictionsmentioning
confidence: 97%
“…However, this prediction is misleading. As we have pointed out elsewhere (Stringer and Brä uer, 1994;Brä uer and Stringer, 1997;Stringer, 2002), the idea of complete replacement without any interbreeding is one variant of the Out of Africa hypothesis, often identified with a particular interpretation of the mitochondrial DNA data, dubbed the Eve theory (Frayer et al, 1993). Complete replacement does not feature in all versions of the Out of Africa hypothesis, and therefore we contend that it would not be falsified by demonstration of some modern-archaic human gene flow outside of Africa.…”
Section: Predictionsmentioning
confidence: 97%
“…With real data, this would require the impossible-averaging mismatch distributions from a series of parallel worlds [22]. 4 Since we have only one world to study, 4 One reviewer disagreed with this claim, so I will provide a proof: Let …”
Section: The Theoretical Mismatch Distributionmentioning
confidence: 99%
“…The multiregional hypothesis of modern human origins [24,4] holds that our species evolved within a widespread population that has inhabited much of Europe, Africa, and Asia for the past million years. This hypothesis implies that the geographic structure of our species goes back at least a million years, originating well before the common mitochondrial ancestor.…”
Section: The Multiregional Hypothesismentioning
confidence: 99%
“…Santa Luca, 1980;Rightmire, 1990Rightmire, , 1991Anton et al, 2007) or even sometimes as 'archaic' Homo sapiens (e.g. Delson et al 1977;Bräuer 1992;Frayer et al, 1993), might instead be identified as a new species dubbed Homo soloensis. This species name was coined by Oppenoorth (1932) in his initial descriptions of the earliest hominin material excavated from Ngandong, and has since been reconsidered by more recent authors (e.g.…”
Section: Regional Continuity In Java: the Idea Of Homo Soloensismentioning
confidence: 99%